Information Literacy and Argumentative Writing Performance among EFL Vocational High School Students: A Correlational Study - Elang Pradhana Dirgantara; Retno Wulan Dari (Retain: Journal of Research in English Language Teaching, 2026)
This study investigated the correlation between information literacy and argumentative writing performance among 11th-grade vocational high school students in Bojonegoro, East Java, Indonesia. Employing a quantitative correlational design, a purposive sample of 52 students was selected from a population of 129. The primary instruments were a 16-item information literacy questionnaire adapted from Regina et al. (2023) and a timed argumentative writing test scored with an analytical rubric adapted from Bean et al. (2021). A Shapiro-Wilk normality test revealed a significant deviation from normality in the writing scores (p = 0.027), which necessitated the use of Spearman’s rho as the non-parametric alternative. The linearity assumption was subsequently confirmed (Deviation from Linearity p = 0.701). The Spearman’s rho analysis yielded a correlation coefficient of rₛ = −0.109 (p = 0.443), indicating a non-significant relationship between the two variables. Consequently, the null hypothesis failed to be rejected. These findings suggest that information literacy alone is an insufficient predictor of argumentative writing performance in this context, and that integrating information literacy instruction alongside explicit writing instruction may be necessary to meaningfully improve students’ writing outcomes.